EMOTIONAL LABOUR IN MANAGEMENT AND BUSINESS STUDIES: AN EVALUATION BASED ON WOS DATABASE - GÜLER , Sevilay (SSD Journal, 2023)
The aim of this study is to examine the scientific publications on emotional labour in the journals in the categories of Management and Business Administration in the Web of Science (WoS) database by descriptive content analysis method. Within the scope of the purpose of the study, the keyword "emotional labour" was searched in the WoS database in the Management and Business categories, Social Sciences Citation (SSCI), Emerging Sources Citation (ESCI) and Science Citation Index Expanded (SCIExpended) indexes, both in the subject titles and in the titles of the studies. As a result of the search, a total of 82 studies related to the subject were reached. The studies were analyzed by descriptive content analysis method according to the year they were published, the journal in which they were published, the type of research they used, the sample group they studied, the number of citations they received and the countries. According to the findings obtained as a result of the analysis, it is seen that the studies on emotional labour have increased after 2018; the studies were mostly written in 2020 and 2022, the journals that publish the most on the subject are "Gender Work and Organization" and "International Journal of Human Resource Management", the "quantitative" research method is mostly preferred in the studies, the sample group in which the related subject is most studied consists of "service sector employees" and "nurses" respectively, the most cited article is Brotheridge, C. M., & Lee, R. T. (2003)’s "Development and validation of the Emotional Labour Scale.", and the country with the highest number of publications is England. Based on the findings, in this study, a general profile of the scientific publications written on the subject was created in order to create a framework for the development of the emotional labour phenomenon, which is handled by different disciplines, in the management and business literature, and suggestions for future research were presented to the relevant researchers.